The Implementation of the Ontological Monism Principle in Islamic Religious Education (PAI) Learning on Students’ Understanding of Faith in Allah - Siti Fatmawati; Irawan Irawan; Erni Haryanti Kahfi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the effect of implementing the Ontological Monism Principle in Islamic Religious Education and Character (PAIBP) learning on students’ understanding of faith in Allah at SMP Negeri 2 Cileunyi, Bandung Regency. This research employs a quantitative approach with a quasi-experimental design using a Static Group Comparison model, involving two groups: an experimental class taught using the Ontological Monism Principle and a control class taught through conventional methods. Data were collected through a posttest instrument in the form of a Likert scale questionnaire that had been tested for validity and reliability. The results show that the experimental class achieved a higher and more homogeneous mean score (53.83) compared to the control class (36.63), and demonstrated a more reflective and contextual understanding. Therefore, the implementation of the Ontological Monism Principle has a positive effect on improving students’ conceptual understanding and spiritual awareness, and can serve as an effective and meaningful alternative model for PAIBP learning.